Viewing Female Depiction in Frozen 2 - Putri, Tia Aprilianti (Language Circle: Journal of Language and Literature, 2021)
Disney is one of the biggest animation companies in the world. They have released many animations since then until now. One of the most popular animations is the princess series. Until 20202, Disney has released fourteen princesses from Snow White and the Seven Dwarfs to Frozen 2. Gender role depictions of the female character(s) were examined with a focus on their behavioral characteristics in the films. The English subtitle of Frozen 2 was used to find out the attitudinal expressions about the female characters. In order to make the research easier and more accurate, a concordance tool named Antconc was used to collect the data and create a corpus. Results found that the most recent princess series entitled Frozen 2 showed the female characters depicted as a precious person who was willing to sacrifice herself for others, kind, heroic, fearless, and full-of-spirit. However, Disney also depicted the female characters as liar and trouble maker. In this case, Disney keeps showing that females cannot be seen using the traditional gender’s perspective anymore. A Female is not only feminine, but she also can be masculine as a man.